2018
DOI: 10.1038/s41419-017-0226-x
|View full text |Cite
|
Sign up to set email alerts
|

Osteopontin promotes metastasis of intrahepatic cholangiocarcinoma through recruiting MAPK1 and mediating Ser675 phosphorylation of β-Catenin

Abstract: The incidence and mortality of intrahepatic cholangiocarcinoma (ICC) are increasing worldwide in recent decades. Osteopontin (OPN) plays an important role in cancer metastasis, but its functional mechanism in ICC is not clear yet. In this study, we found that OPN level was elevated both in plasma and tumor tissues of ICC patients, which was closely related to a shorter overall survival (OS) and high probability of tumor relapse after curative resection. The gain- and loss-of-function studies determined that OP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 38 publications
0
38
0
Order By: Relevance
“…93 Of note, OPN promotes iCCA growth and metastasis by recruiting MEK/MAPK1 and activating Wnt/β-Catenin signaling. 94 Clinical relevance of OPN as putative biomarker was confirmed by molecular profiling of laser-capture microdissected stroma derived from human iCCA, showing marked increase in OPN gene expression levels compared with nontumor tissue, and also, a significant correlation with poor prognosis. 95 Noteworthy, stromal overexpression of OPN and TGF-β2 had the strongest independent predictive power on overall and disease-free survival.…”
Section: Perlecanmentioning
confidence: 94%
“…93 Of note, OPN promotes iCCA growth and metastasis by recruiting MEK/MAPK1 and activating Wnt/β-Catenin signaling. 94 Clinical relevance of OPN as putative biomarker was confirmed by molecular profiling of laser-capture microdissected stroma derived from human iCCA, showing marked increase in OPN gene expression levels compared with nontumor tissue, and also, a significant correlation with poor prognosis. 95 Noteworthy, stromal overexpression of OPN and TGF-β2 had the strongest independent predictive power on overall and disease-free survival.…”
Section: Perlecanmentioning
confidence: 94%
“…Prior studies have reported that the phosphorylation of ␤-catenin at Ser 33 -Ser 37 -Thr 41 is essential for ubiquitinationmediated degradation of ␤-catenin (29,30) and the phosphorylation of ␤-catenin at Ser 675 is responsible for ␤-catenin transcriptional activation (31). In our study, we found that the phosphorylated ␤-catenin at Ser 33 -Ser 37 -Thr 41 decreased by 20.1, 42.6, or 65.6%, respectively, in the livers of WT mice treated with 1, 10, or 100 ppm benzene via inhalation.…”
Section: Pp2a Regulates Benzene-induced Hematotoxicity By Suppressionmentioning
confidence: 99%
“…␤-Catenin was sequentially phosphorylated at Ser 33 -Ser 37 -Thr 41 by CKI␣ and GSK3, leading to degradation via the ubiquitination/proteasome machinery (43). In contrast, phosphorylation of ␤-catenin at Ser 675 promoted the nuclear accumulation of ␤-catenin and activation of target gene tran-scription (31). In the current study, we found that the dephosphorylation of ␤-catenin at Ser 33 /Ser 37 /Thr 41 in benzenetreated mouse liver led to up-regulation of ␤-catenin and, in turn, activation of cyp2e1 transcription.…”
Section: Pp2a Regulates Benzene-induced Hematotoxicitymentioning
confidence: 99%
“…OPN is involved in NAFLD pathogenesis (Kiefer et al., 2011), and its liver expression is increased in obesity and correlates with steatosis and insulin resistance (Gómez‐Ambrosi et al., 2007). OPN expression is also upregulated in liver cancers such as in HCC and cholangiocarcinoma (Wen, Jeong, Xia, & Kong, 2016; Zheng et al., 2018). Regarding its role as a metabolic modulator, it controls the fate of acetyl‐CoA in liver (Nunez‐Garcia et al., 2017; Nuñez‐Garcia et al., 2018) and rewires liver lipid metabolism after partial hepatectomy (Nuñez‐Garcia et al., 2018).…”
Section: Introductionmentioning
confidence: 99%